2021
DOI: 10.1096/fj.202002253rrr
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS11a is a novel age‐altered, tissue specific regulator of migration and wound healing

Abstract: Aging is a gradual biological process characterized by a decrease in cellular and organism functions. Aging-related processes involve changes in the expression and activity of several proteins. Here, we identified the transmembrane protease serine 11a (TMPRSS11a) as a new age-specific protein that plays an important role in skin wound healing. TMPRSS11a levels increased with age in rodent and human skin and gingival samples. Strikingly, overexpression of TMPRSS11a decreased cell migration and spreading, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…This protein is a Type II transmembrane serine protease (TTSP) participating in diverse biological processes. As reported recently by our group, a differentiated expression of TMPRSS11a with age was identified in gingival and skin fibroblasts, which has been associated with senescence processes and wound healing (Fernandez et al, 2021). Moreover, it was demonstrated that TMPRSS11a participates in critical cellular responses, including cell migration and spreading.…”
Section: Case Studies: the Interactome Of Trpm4 And Tmprss11asupporting
confidence: 75%
See 1 more Smart Citation
“…This protein is a Type II transmembrane serine protease (TTSP) participating in diverse biological processes. As reported recently by our group, a differentiated expression of TMPRSS11a with age was identified in gingival and skin fibroblasts, which has been associated with senescence processes and wound healing (Fernandez et al, 2021). Moreover, it was demonstrated that TMPRSS11a participates in critical cellular responses, including cell migration and spreading.…”
Section: Case Studies: the Interactome Of Trpm4 And Tmprss11asupporting
confidence: 75%
“…Interestingly, integrins are recognized targets of proteins containing an arginine-glycine-aspartic acid (RGD) motif ( Moreno-Layseca et al, 2019 ), which was identified in TMPRSS11a. Considering this evidence, protein-protein docking, and molecular dynamics simulations were performed, identifying a favored TMPRSS11a:Integrin complex detailed at Fernandez et al, 2021 . The physical association of both proteins was predicted to occur between the RGD motif of TMPRSS11a and a pocket located at the top face of the α 5 β 1 integrin.…”
Section: Case Studies: the Interactome Of Trpm4 And Tmprss11amentioning
confidence: 99%
“…Migration was allowed to occur for 24 h. Following the removal of the non-invading cells, the invading cells were fixed and stained with 0.2% crystal violet. Cell migration was evaluated by counting five (× 20) fields per chamber ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…These mediators have been implicated both in the recruitment of neutrophils into the epidermis and the presence of p21-induced cellular senescence and thus may have a negative impact on wound re-epithelialization. [84][85][86] Pairwise comparisons between ulcer types resulted in enrichment of certain pathways in LUs, including those reflecting elevated levels of inflammatory activity, hypoxia, and reperfusion. These responses may induce an adaptive response that results in an increased rate of glycolysis in order to conserve energy or promote cell death.…”
Section: Discussionmentioning
confidence: 99%